The Impact of Financial Due Diligence Findings on Enterprise Value - Sørensen, Olivia (My University, 2025)
This thesis examines how findings uncovered during the financial due diligence process relate to firm’s valuation outcomes in mergers and acquisitions (M&A) transactions. This study aims to assess if valuation multiples are affected by common objects examined during financial due diligence – revenue volatility, working capital and cashflow sustainability. The motivation for this study arises from the lack of empirical research conducted regarding this topic precisely. The literature review presents the reader the understanding of why due diligence is a necessary tool to reduce information asymmetry and mitigate post-acquisition integration challenges. The empirical part of the study exploits the ordinary least squares (OLS) regression framework to assess the relationship between the due diligence findings and the valuation outcome. The sample consists of 50 acquired firms from years 2009-2025 operating in five different industries to ensure the dataset presents versatility and comprehensiveness. The firm-level financial data retrieved from Bloomberg database emphasized on the year prior to the deal announcement to make sure that the regression results were not biased by the deal announcement. The study confirmed that leverage, Tobin’s Q and the technology industry significantly impacted the valuation multiple Enterprise Value to Earnings Before Interest, Taxes, Depreciation, and Amortization (EV/EBITDA) ratio. This result is consistent with financial literature stating that higher risk caused by leverage leads to lower valuation results whereas Tobin’s Q and the technology industry indicating positive growth expectations produce higher valuation multiples. Nevertheless, the independent financial due diligence variables were not statistically significant, which indicates that the process’s impact can be found through negotiation terms and other qualitative measures. Financial due diligence operates via deal terms rather than valuation multiples. This highlights the role of due diligence being a monitoring and verification mechanism which contributes to a better-informed decision-making process.

Tämä tutkielma tarkastelee, kuinka due diligence -prosessin aikana esiin tulleet havainnot liittyvät yrityksen arvonmäärityksen lopputuloksiin yrityskaupoissa. Tutkimuksen tavoitteena on selvittää, vaikuttavatko taloudellisessa due diligence -prosessissa tyypillisesti tarkasteltavat osa-alueet, kuten liikevaihdon volatiliteetti, käyttöpääoma ja kassavirran kestävyys, arvostuskertoimiin. Kirjallisuuskatsaus antaa lukijalle ymmärryksen siitä, miksi due diligence on välttämätön väline epäsymmetrisen informaation vähentämiseksi ja yritysostojen jälkeisten integraatiohaasteiden lieventämiseksi. Tutkimuksen empiirinen osa hyödyntää pienimmän neliösumman menetelmää, jotta voidaan arvioida due diligence -löydösten ja arvonmäärityksen välistä yhteyttä. Aineisto koostuu 50 yrityksestä, jotka toimivat viidellä eri toimialalla, jotta aineiston voidaan olettaa olevan monipuolinen ja kokonaisvaltainen. Näitä yrityksiä koskevat taloudelliset tiedot on haettu Bloomberg-tietokannasta. Haun aikarajauksena on käytetty vuotta ennen yrityskauppailmoitusta. Tutkimuksen tuloksena todettiin, että velka, Tobinin Q ja teknologia sektori vaikuttivat merkittävästi yritysten arvostuskertoimeen, joka on määritelty seuraavasti: yritysarvo jaettuna tuloksella ennen veroja, velkojen korkoja, poistoja ja arvonalentumisia. Tämä tulos on yhdenmukainen taloudellisen kirjallisuuden kanssa, jonka mukaan suurempi riski, jota velka aiheuttaa, johtaa alempiin arvostuskertoimiin, kun taas positiiviset kasvuodotukset näyttäytyvät korkeampina arvostuskertoimina. Vaikka taloudellisen due diligence -prosessin löydökset eivät olleet tilastollisesti merkittäviä, prosessin vaikutus voidaan havaita neuvotteluehdoissa ja muissa laadullisissa tekijöissä. Tutkimuksen tuloksena taloudellisen due diligence:n vaikutukset voidaan havaita sopimusten ehdoissa eikä niinkään arvostuskertoimissa. Tämä korostaa due diligence -prosessin roolia valvonta- ja varmennusmekanismina, joka edistää paremmin informoitua päätöksentekoprosessia.
Keywords: Due diligence, Valuation, Asymmetric information, Agency theory, Mergers and Acquisitions, Qualitative measures, Asianmukainen Huolellisuus (Due Diligence), Arvonmääritys, Epäsymmetrinen Informaatio, Agenttiteoria, Yrityskaupat, Laadulliset Tekijät